Democracy, Transparency, and Secrecy in Crisis. Issue 4 (30th April 2018) - Bell, Sam R; Martinez Machain, Carla
Abstract: Why is it that some democracies are able to effectively engage in secrecy and mobilize their forces privately, while others are unable to keep enough information secret to effectively carry out such an attack? Recent work by Colaresi (2014) suggests that a democracy's ability to keep information secret depends on its retrospective oversight institutions, which allow democracies to keep information secret in the present with the promise of revealing it to the public in the future. Though Colaresi (2014) finds that states with retrospective oversight have greater military spending, more support for military action, and more success in crises, to our knowledge there has yet to be empirical support for the argument that democracies with greater retrospective oversight can actually conduct foreign policy with greater opacity than those without retrospective oversight. In this research note we empirically explore this question, using data on private mobilizations by democracies with varying levels of retrospective oversight. This gives us greater insight into strategic military choices and shows how military effectiveness can be affected by political institutions.